rosmarinic acid effect on bonding performance to caries affected dentine (Mustansiria Dental Journal, 2024)
Aim: This study investigated the effect of applying rosmarinic acid (RA) as dentine surface pretreatment on the immediate microtensile bond strength (µTBS) after 24h of water storage and delayed µTBS after 5000 thermocycles using 1-step self-etch adhesive (1-SEa) on artificial caries affected dentine (ACAD).Method: In this experimental in vitro study, the dentine surface of 40 premolars were exposed and subjected to a pH-cycling procedure for ACAD induction. Next, teeth were divided randomly into two groups (n=20 each): ROS-group that was treated with RA solution (100µM RA in 5% ethanol) for 5s then dried for 5s, and control untreated group. One sample was taken from each group for surface analysis with SEM. Following bonding and composite build up procedures, the specimens were sectioned into 1mm2 beams and subjected to microtensile test after 24h (immediate) or 5000 thermal cycles (delayed). The fractured beams were examined under stereomicroscope to determine failure type. Data were analysed with t-test of independent variables, significance level was set at 0.05.Results: ROS-group showed a significant increase in the immediate µTBS compared to control (p=0.003), while the µTBS of both groups were decreased significantly following thermocycling (p